FAKTOR-FAKTOR YANG MEMPENGARUHI PERKEMBANGAN USAHA KECIL SEKTOR INDUSTRI PENGOLAHAN DI KOTA MALANG - Cahyanti, Mega Mirasa; Anjaningrum, Widiya Dewi (LP2M Institut Teknologi dan Bisnis Asia Malang, 2017)
This study aims to determine the factors that influence the development of the small business manufacturing sector in Malang town. This research is a kind of field research, where the primary quantitative data through questionnaire was taken directly from small businesses. The sampling technique that was used is purposive sampling, where the sample was selected based on the consideration which the sample could provide some informations that are suitable with the needs of the research. Based on the Slovin formula, a predetermine number of samples that taken was 89 small businesses. Based on the result taken by data processing and factor analysis using SPSS 23, shows that the factors which influence the development of small business manufacturing sector are the quality of human resources, production systems, financial management systems, marketing strategies, the partnership system, the quality of infrastructure and regulation. In this case, the factor which has the higest significant effect is partnership system. Finally, improving the partnership system on small business should be developed not only with suppliers, but also with the government, large business, financial institutions and business centers. Therefore, these small business could be thrive.